The role of the nurse in the diagnostics of allergic diseases - skin tests - Ziętkowska, Elżbieta; Ziętkowski, Ziemowit; Bodzenta-Łukaszyk, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Allergic diseases are very common in the present civilization. Most of these disorders are chronic and systematic therapy is needed. Allergy treatment is difficult and should be multidirectional. The essential tests, used in the diagnostics of allergic diseases, are skin tests. They are the most effective method in allergy detection and allergen identification. In the dependence of the site of application skin tests are divided on intradermal, prick and epidermal - patch tests. The nurse plays an important role in the diagnostics of allergic patient. She should inform the patient about the aim and course of performed procedure, as well as correct applicate, read off and document the results of tests. Moreover, she takes care on the patient before, through and after performed tests. Nursing Topice 2010; 18 (4): 523-528